Music Perception Influences Language Acquisition: Melodic and Rhythmic-Melodic Perception in Children with Specific Language Impairment - Stephan Sallat; Sebastian Jentschke (Behavioural Neurology)
Language and music share many properties, with a particularly strong overlap for prosody. Prosodic cues are generally regarded as crucial for language acquisition. Previous research has indicated that children with SLI fail to make use of these cues. As processing of prosodic information involves similar skills to those required in music perception, we compared music perception skills (melodic and rhythmic-melodic perception and melody recognition) in a group of children with SLI (N=29, five-year-olds) to two groups of controls, either of comparable age (N=39, five-year-olds) or of age closer to the children with SLI in their language skills and about one year younger (N=13, four-year-olds). Children with SLI performed in most tasks below their age level, closer matching the performance level of younger controls with similar language skills. These data strengthen the view of a strong relation between language acquisition and music processing. This might open a perspective for the possible use of musical material in early diagnosis of SLI and of music in SLI therapy.